The Number and Size of Invasion Areas in Mixed-Type Carcinoma in Female Dogs Are Associated with Regional Metastases - Fernanda Freitas Miranda; Ana Paula Vargas Garcia; Marina Possa dos Reys; Erica Almeida Viscone; Mayra Cunha Flecher; Michele Angela Rodrigues; Geovanni Dantas Cassali (Veterinary Sciences)
Mixed-type carcinoma (MTC) accounts for 44% of mammary neoplasms in bitches and poses challenges in histological grading due to the heterogeneity of invasive areas. The present study aimed to measure and characterize invasive areas in the stroma of MTC and investigate the association of those parameters with lymph node status and survival. Forty cases were analyzed and divided into two groups: with metastasis and without metastasis. The size, perimeter, length, and number of invasive carcinomatous areas were measured. Cases with metastasis showed a higher number of foci (p = 0.003) and larger invasive areas (p = 0.006) compared to cases without metastasis. Bitches with invasive areas larger than 2 mm2 had shorter survival times. No association was found between the perimeter or length of invasive areas, the expression of Ki67, ER, PR, COX-2, HER-2, and the immunophenotype. Thus, the number and size of invasive areas are associated with regional lymph node status, suggesting histomorphometry may serve as a valuable tool for evaluating the biological behavior of mixed-type carcinoma.